300 PCSK9 induces a prothrombotic response by activation of NFKB signalling pathway in mononuclear cells. (8th December 2021) - Scalise, Valentina; Sanguinetti, Chiara; Neri, Tommaso; Celi, Alessandro; Pedrinelli, Roberto
Abstract: Aims: Strong evidence both experimental and clinical studies point out to an involvement of proprotein convertase subtilisin/kexin 9 (PCSK9), as an important player in hypercholesterolemia and atherosclerosis pathophysiology, identifying it, as a key molecule in the development of new cholesterol-lowering drugs and therapeutic target for atherosclerosis and related diseases. Emerging evidence shown that PCSK9 is straight implicated in inflammatory process where it may directly influence the activity of various cell types through NFkB activation, a key transcription factor involved in the induction of both pro-inflammatory cytokines and Tissue Factor (TF) expression, a major regulator of haemostasis and thrombosis in monocytes. Deductive reasoning makes therefore plausible to investigate a mechanistic link between circulation PCSK9 levels and TF expression, both in monocytes as well as on the surface of microparticles (MPs) generated from the same cells, with NFkB acting as the chain in the link. To investigate the involvement of NFkB signalling pathway in PCSK9-induced TF expression. Methods: THP-1 cell line were stimulated with human (h) PCSK9 (5 μg/mL) or pre-incubated with BAY-117082 (BAY, 10 −5 M) an NFκB inhibitor, CLI-095 (3 × 10 −6 M), a highly TLR-4 signalling specific inhibitor and LPS-RS(5 μg/mL) a TLR-4 antagonist. TF procoagulant activity (PCA) was assessed by one-stage clotting assay using a STart Max semi-automated coagulation analyser. Concentration of TF-bearing MPs was determined using the Zymuphen MP-activity kit. Results: hPCSK9 stimulated TF activity in THP-1 (PCA: from 50 ± 20 to 120 ± 20 ρg/mL, n = 10, P < 0.01). BAY, an NFkB inhibitor (PCA: −71 ± 23%, n = 5, P < 0.01) and CLI-095, a TLR-4 signalling inhibitor, (PCA: −86 ± 26%, n = 3, P < 0.05) and LPS-RS (PCA: −71 ± 23%, n = 5, P < 0.01) down-regulated PCSK9-induced TF activity completely. Furthermore THP-1stimulation with hPCSK9 causes the release of prothrombotic MPs-TF + (MPs release from: 0.13 ± 0.07 to 0.42 ± 0.1 nM PS, n = 7, P < 0.05; PCA-MP + from: 14 ± 3 to 44 ± 28 ρg/mL, n = 5, P < 0.05). Conclusions: These data confirm the pivotal role of monocytes in the response PCSK9-induced TF-expression as well as the involvement of PCSK9 in inflammatory-thrombotic diseases through a direct stimulation of TF procoagulant activity and by the release of TF-bearing MPs. The possible mechanism of action involves recognition of PCSK9 by TLRs 2 and/or 4, on monocytes membrane surface, leading to activation of the transcription factor NFκB via an intracellular signalling cascade. Further studies will be needed to better understand the regulatory mechanisms underlying this complex set of biological responses that bind PCSK9, and coagulation events.